Transcriptional signatures of schizophrenia in hiPSC-derived NPCs and neurons are concordant with post-mortem adult brains - Gabriel E. Hoffman (Nature Portfolio, 2017)
Induced pluripotent stem cell (hiPSC)-based models have inherent variations in their cellular and molecular output and readouts. Here, Hoffman and colleagues devise a method to account for gene expression variations in hiPSC-derived neurons from patients with childhood-onset schizophrenia.